AN ANALYSIS OF PERSONIFICATION OF ROBERT FROST’S POETRY - Anggi Engka; Nihta Liando; Alloysius Rettob (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This study was aimed at identifying personified sentences in Robert Frost's poems. In conducting research, descriptive qualitative method have been used.The data were collected by choosing and marking the personification expressions from Robert Frost's poems and then making a note of the data. The data were analyzed following the procedural steps by Miles and Huberman. By analyzing the data based on the related theory, the result of this research found nine expressions of personification in two form namely Prosopopopeia and prosopographia. There were six found in the form of prosopopopeia and three others found in prosopographia form. As a poet, Robert Frost has 36 poems that he has written. Based on the result of the study, future researcher can conduct the similar research but in different subject. The next researcher can use the other poems or students of university as the same of data, in conducting research that similar with this topic. The next researcher also can take the information from this study in order to get the better study